A polymer microsphere and its preparation method and lithium ion battery separator

By introducing a shell layer with low glass transition temperature into the polymer microspheres, a hard-core soft-shell structure is formed, which solves the problem of poor thermal pressing effect of polymer microspheres, and improves the bonding strength and electrochemical of the lithium-ion battery separator. performance.

CN118459671BActive Publication Date: 2025-02-18SUZHOU DERBY ELECTRONIC MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410478694.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-19
Publication Date
2025-02-18
Estimated Expiration
2044-04-19

AI Technical Summary

Technical Problem

In the prior art, the thermal pressing effect of polymer microspheres is poor, which affects the electrochemical performance of lithium-ion batteries.

Method used

By introducing a shell layer with low glass transition temperature, polymer microspheres with hard-core soft-shell structures are formed to improve their bonding strength and hot-pressing effect.

Benefits of technology

In the lithium-ion battery separator, the soft shell of the polymer microspheres is transformed into a viscous fluid state during the hot pressing process, which improves the bonding effect between the separator and the electrode sheet, and improves the energy density and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118459671B_ABST
    Figure CN118459671B_ABST
Patent Text Reader

Abstract

The present invention provides a polymer microsphere and a preparation method thereof and a lithium-ion battery separator, and relates to the technical field of lithium-ion battery preparation; the polymer microsphere comprises a core body and a shell coated on the outside of the core body; wherein the glass transition temperature of the shell is lower than the glass transition temperature of the core body; and the glass transition temperature range of the shell is 50°C-100°C. The polymer microsphere provided by the present invention adopts a hard-core and soft-shell structure, and while avoiding deformation of the polymer microsphere during ball milling, hot pressing and the like, and ensuring its structural stability, the soft shell can be transformed into a viscous flow state as the temperature rises during the hot pressing process, so that after being applied to the separator, it can play a role in bonding the separator and the electrode plate, thereby improving the hot pressing effect of the polymer microsphere.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery preparation, and in particular to a polymer microsphere and a preparation method thereof, and a lithium ion battery separator. Background Art

[0002] As the main component unit of lithium-ion batteries, the diaphragm separates the two poles and provides lithium ion and electrolyte channels, which has an important impact on the safety, capacity, charge and discharge power, and cycle performance of lithium-ion batteries. The main commercial products are polyethylene (PE) diaphragms and polypropylene (PP) diaphragms. However, due to their poor heat resistance, they shrink significantly at high temperatures and can easily cause a short circuit between the two poles, which can cause battery deformation at the least and burn at the worst, threatening the safety of people and property.

[0003] At present, ceramic slurry is usually coated on the surface of the diaphragm substrate to form a heat-resistant ceramic layer with a thickness of 2-5μm to improve the heat resistance of the diaphragm substrate. However, due to the high specific gravity of ceramic particles, the presence of the ceramic heat-resistant layer will increase the mass and thickness of the composite diaphragm, which is not conducive to the improvement of the energy density of lithium-ion batteries. Based on this problem, there are documents that introduce polymer microspheres, such as PMMA microspheres, on the diaphragm substrate to improve the battery energy density.

[0004] However, the polymer microspheres currently used in separators have low bonding strength and poor hot pressing effects, which affects the electrochemical performance of lithium-ion batteries. Summary of the invention

[0005] In order to solve the problem of poor hot pressing effect of polymer microspheres in the prior art, the present invention provides a polymer microsphere, which introduces a low-Tg shell layer so that the shell layer can play a role in bonding the diaphragm and the electrode plate after hot pressing, thereby improving the bonding strength, thereby solving the problem of poor hot pressing effect of polymer microspheres in the prior art.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] A polymer microsphere comprises a core body and a shell coated on the outside of the core body; wherein the glass transition temperature of the shell is lower than the glass transition temperature of the core body; and the glass transition temperature of the shell ranges from 50°C to 100°C.

[0008] Optionally, the core has a glass transition temperature in the range of 90°C to 120°C.

[0009] Optionally, the outer diameter of the polymer microspheres is (4.5-5.5) μm.

[0010] Another object of the present invention is to provide a method for preparing the polymer microspheres as described above, comprising the following steps:

[0011] S1: Using soft monomer and hard monomer in a mass ratio of 1:(20-45) as raw materials, seed microspheres are generated by soap-free emulsion polymerization;

[0012] S2: using the seed microsphere as the core, copolymerizing the soft monomer and the hard monomer in a mass ratio of 1:(3-13) to form a microsphere emulsion;

[0013] S3: using the microsphere emulsion as a raw material and adopting a high temperature atomization drying process to prepare polymer microspheres.

[0014] Optionally, the soft monomers in step S1 and step S2 are both selected from at least one of butyl acrylate and isooctyl acrylate.

[0015] Optionally, the hard monomers in step S1 and step S2 are both selected from at least one of methyl methacrylate, styrene, acrylonitrile, sodium p-styrene sulfonate, acrylic acid, and methacrylic acid.

[0016] Optionally, step S1 includes: mixing the soft monomer, the hard monomer and water according to the formula, stirring and shearing in an inert gas atmosphere, heating to 60-80° C., dropping an initiator, reacting to generate seed microspheres, and obtaining a reaction solution.

[0017] Optionally, step S2 comprises: adding a soft monomer, a hard monomer and an initiator to the reaction solution according to the formula amount, and after the reaction, dripping a crosslinking agent, and continuing the reaction to obtain a microsphere emulsion.

[0018] Optionally, the atomization drying temperature of the high-temperature atomization drying process in step S3 is 60°C-200°C.

[0019] Another object of the present invention is to provide a lithium ion battery separator, comprising the polymer microspheres as described above.

[0020] The beneficial effects of the present invention are:

[0021] The polymer microspheres provided by the present invention adopt a hard core and soft shell structure, which prevents the polymer microspheres from being deformed during ball milling, hot pressing and the like, and ensures their structural stability. In this way, the soft shell can be transformed into a viscous flow state as the temperature rises during the hot pressing process, so that after being applied to the diaphragm, the soft shell can play a role in bonding the diaphragm and the electrode plate, thereby improving the hot pressing effect of the polymer microspheres. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0023] Figure 1 is a photograph of the primary polymer microspheres prepared in Example 1 of the present invention;

[0024] Figure 2 is a photograph of secondary polymer microspheres prepared in Example 1 of the present invention;

[0025] Figure 3 This is a statistical test chart of the particle size of polymer microspheres in Example 1 of the present invention;

[0026] Figure 4 This is a statistical test chart of the particle size of polymer microspheres in Example 2 of the present invention. DETAILED DESCRIPTION

[0027] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0028] In order to solve the problem of poor hot pressing effect of polymer microspheres in the prior art, the present invention provides a polymer microsphere, which includes a core body and a shell coated on the outside of the core body; wherein the glass transition temperature of the shell is lower than the glass transition temperature of the core body, thereby forming a hard core and soft shell structure; during application, the hard core can resist structural deformation of the sphere during ball milling, hot pressing and the like; the present invention further preferably has a glass transition temperature range of 50°C-100°C, so that the soft shell can play a role in bonding the diaphragm and the electrode plate after hot pressing, thereby improving the hot pressing effect of the polymer microsphere.

[0029] The polymer microspheres provided by the present invention adopt a hard core and soft shell structure, which prevents the polymer microspheres from being deformed during ball milling, hot pressing and the like, and ensures their structural stability. In this way, the soft shell can be transformed into a viscous flow state as the temperature rises during the hot pressing process, so that after being applied to the diaphragm, the soft shell can play a role in bonding the diaphragm and the electrode plate, thereby improving the hot pressing effect of the polymer microspheres.

[0030] In order to avoid the stability of the polymer microsphere structure, the glass transition temperature of the core body is preferably in the range of 90°C-120°C.

[0031] Furthermore, the outer diameter of the polymer microspheres of the present invention is preferably (4.5-5.5) μm to ensure that the particle size of the polymer microspheres is larger than the thickness of the coating on the diaphragm after drying, so that the polymer microspheres are exposed on the coating and after hot pressing treatment, they can better exert the bonding effect and improve the bonding effect between the diaphragm and the electrode material.

[0032] In addition, by combining the large particle size of the polymer microspheres with the hard core, the polymer microspheres deform less during the hot pressing process of the lithium-ion battery cells, can provide a certain internal gap, promote lithium ion conduction, inhibit battery cell expansion, and do not cause a large degree of blockage in the gaps of the diaphragm, which is beneficial to improving the battery energy density and safety performance.

[0033] Another object of the present invention is to provide a method for preparing the polymer microspheres as described above, the preparation method comprising the following steps:

[0034] S1: Using soft monomer and hard monomer in a mass ratio of 1:(20-45) as raw materials, seed microspheres are generated by soap-free emulsion polymerization;

[0035] In this step, the soft monomer and the hard monomer are combined to generate seed microspheres with a relatively high glass transition temperature, and the seed microspheres are further used as the core of the polymer microspheres; specifically, the glass transition temperature of the core is in the range of 90°C-120°C.

[0036] S2: With seed microspheres as cores, a microsphere emulsion is formed by copolymerizing soft monomers and hard monomers in a mass ratio of 1:(3-13);

[0037] In this step, a shell with a relatively low glass transition temperature is generated on the outside of the seed microsphere by combining the soft monomer with the hard monomer, which is recorded as a primary polymer microsphere; specifically, the glass transition temperature of the shell is in the range of 50°C-100°C.

[0038] S3: Using microsphere emulsion as raw material, high temperature atomization drying process is adopted to prepare polymer microspheres.

[0039] In order to increase the particle size of the polymer microspheres and further improve the bonding effect, in step S3, based on the soft shell characteristics of the primary polymer microspheres, the low glass transition temperature Tg of the outer shell copolymer of the primary polymer microspheres is utilized, and a high-temperature atomization drying method is adopted. During the high-temperature atomization drying process, the outer shells of the primary polymer microspheres are bonded to each other to form secondary polymer microspheres with larger particle sizes, i.e., the target product polymer microspheres.

[0040] The preparation method of polymer microspheres provided by the present invention comprises the following steps: firstly, a certain proportion of soft and hard monomers are used to generate seed microspheres with a high Tg by soap-free emulsion polymerization, and the seed microspheres are used as the core, and a specific proportion of soft and hard monomers are copolymerized to form an outer shell layer with a low Tg, thereby preparing primary polymer microspheres with a hard-core and soft-shell structure with uniform particle size; further, a high-temperature atomization drying process is adopted to prepare the primary polymer microspheres into large-particle-size secondary polymer microspheres for battery separators; the polymer microspheres have a hard-core and soft-shell structure, and the soft shells can be transformed into a viscous flow state as the temperature rises during the hot pressing process while avoiding deformation of the polymer microspheres during ball milling, hot pressing and the like, and ensuring the structural stability thereof, so that after being applied to the separator, the separator and the electrode plate can be bonded, thereby improving the hot pressing effect of the polymer microspheres.

[0041] In the present invention, the soft monomers in step S1 and step S2 are preferably selected from at least one of butyl acrylate and isooctyl acrylate; the hard monomers in step S1 and step S2 are preferably selected from at least one of methyl methacrylate, styrene, acrylonitrile, sodium p-styrene sulfonate, acrylic acid, and methacrylic acid; and the hard monomer is further preferably methyl methacrylate.

[0042] Specifically, the preferred step S1 of the present invention is carried out as follows: according to the formula, the soft monomer, the hard monomer and water are mixed, stirred and sheared under an inert gas atmosphere, heated to 60-80° C., an initiator is added dropwise, reacted, seed microspheres are generated, and a reaction solution is obtained.

[0043] The preferred initiator of the present invention is a water-soluble initiator, and further preferably the initiator is selected from at least one of potassium persulfate (KPS), ammonium persulfate (APS), ammonium persulfate-Bruggolite FF6, and potassium persulfate-sodium sulfite; the preferred high-speed shearing speed is 8000-9000r / min; and the preferred reaction time is 1-2h.

[0044] The preferred step S2 of the present invention is carried out as follows: according to the formula amount, soft monomer, hard monomer and initiator are added to the reaction solution, after the reaction, a crosslinking agent is added dropwise, and the reaction is continued to obtain a microsphere emulsion.

[0045] In the present invention, the initiator in this step is preferably a water-soluble initiator, and further preferably the initiator is selected from at least one of potassium persulfate (KPS), ammonium persulfate (APS), ammonium persulfate-Bruggolite FF6, and potassium persulfate-sodium sulfite; the cross-linking agent is preferably selected from at least one of hydroxymethyl acrylamide, glycidyl methacrylate, hydroxyethyl acrylate, hydroxyethyl acrylamide, and divinylbenzene; and further preferably the cross-linking agent is a mixture of hydroxyethyl acrylamide and divinylbenzene.

[0046] To ensure the smooth generation of secondary polymer microspheres, the atomization drying temperature of the high-temperature atomization drying process in step S3 of the present invention is preferably 60°C-200°C, and further preferably 100°C-160°C, to ensure that the shells of the primary polymer microspheres are bonded to each other during the high-temperature atomization drying process, thereby achieving the production of secondary microspheres.

[0047] Specifically, step S3 is preferably carried out according to the following process: using a high-temperature atomization drying process, first the microsphere emulsion is pumped to the top of the drying chamber under high pressure to be atomized into fine droplets, and then the microspheres are agglomerated and bonded into secondary polymer microspheres through reverse or co-directional gradient hot air drying in the drying chamber, and then the microspheres are blown to a secondary drying port for further drying to obtain the target product, polymer microspheres.

[0048] Among them, the drying chamber temperature is 60-200°C, the drying air volume is 10-500CFM, the residence time is 1-100s, the emulsion atomization pressure is 0.1-1MPa, the inner diameter of the atomization nozzle is 0.3-2mm, the secondary drying nozzle temperature is 30-120°C, and the nozzle diameter is 0.1-5mm; the preferred process: the drying chamber temperature is 100-160°C, the drying air volume is 70-200CFM, the drying chamber residence time is 2-10s, the emulsion atomization pressure is 0.5-0.7MPa, the inner diameter of the atomization nozzle is 0.7mm, the secondary drying nozzle drying temperature is 50-90°C, and the nozzle inner diameter is 0.7-1.0mm.

[0049] The present invention firstly prepares seed microspheres with a high Tg by soap-free emulsion technology, and further synthesizes primary polymer microspheres (particle size 200-600nm) with a hard core and soft shell structure with uniform particle size. No emulsifier is added during the reaction (small dissolution). By introducing a cross-linking system during the reaction, the cross-linking degree of the microspheres is increased, and the dissolution and swelling in the electrolyte are reduced. The low glass transition temperature Tg of the outer shell copolymer of the microspheres is utilized, and a high-temperature atomization drying method is adopted to process and prepare the microspheres into secondary polymer microspheres with a particle size of several microns. By adjusting the ratio of soft and hard monomers, cross-linking monomers, and the synthesis process of adding materials, the particle size and distribution of the microspheres, the glass transition temperature Tg, swelling, dissolution, and hot pressing bonding and peeling performance are adjusted. By adjusting the high-temperature atomization drying process, large-sized polymer microspheres with different surface morphologies are obtained.

[0050] In the prepared polymer microspheres, the hard core can resist the structural deformation of the spheres during ball milling, hot pressing and other processes, and the soft shell facilitates the mutual bonding of primary microspheres into secondary microspheres. At the same time, the soft shell plays a role in bonding the diaphragm and the electrode plate after hot pressing.

[0051] Another object of the present invention is to provide a lithium ion battery separator, which comprises the polymer microspheres as described above.

[0052] The lithium ion battery separator of the present invention can be prepared according to the following method:

[0053] According to the formula, polymer microsphere powder, binder, sodium carboxymethyl cellulose, polyether siloxane wetting agent, dispersant and water are added in appropriate amounts and made into a mixture slurry by ball milling (speed 580r / min, ball milling for 1h). The mixed slurry is coated on the PP diaphragm substrate to form a wet film coating with a thickness of 6-9μm, and fully dried at 60℃ to obtain a single-sided mixed-coated lithium-ion battery diaphragm.

[0054] The lithium ion battery separator provided by the invention has high bonding strength, small swelling in electrolyte and good hot pressing effect after being used in lithium ion batteries.

[0055] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0056] Example 1

[0057] This embodiment provides a method for preparing polymer microspheres, which is carried out as follows:

[0058] S1: 20g methyl methacrylate, 1g butyl acrylate, 1g methacrylic acid, and 100g water were mixed, nitrogen was passed through, high-speed stirring and shearing was performed at 8000r / min, and water bath heating was started (the temperature was set to 70°C). At 70°C, 20g aqueous solution containing 0.1g APS was added dropwise, and the mixture was reacted for 1h to generate seed microspheres to obtain a reaction solution;

[0059] S2: Add 120g methyl methacrylate, 20g butyl acrylate, 4g acrylic acid, and 80g KPS solution with a mass fraction of 0.5% to the reaction solution and react for 30 minutes, then drop 10g hydroxyethyl acrylamide and 2g DVB, and keep warm at 70°C for 10 hours. Filter the material through a 300-mesh filter to obtain a milky white emulsion, i.e., a microsphere emulsion;

[0060] S3: The microsphere emulsion obtained above is sent to a spray drying chamber for high-pressure atomization (funnel-shaped drying chamber with a volume of 4 L) by an intermittent peristaltic pump. The gradient temperature of the spray chamber is set to 130°C, the atomization pressure is 0.5 MPa, and a plurality of atomizing nozzles are provided on the atomizing disk. The inner diameter of the nozzle is 0.5 mm, the feed rate of the peristaltic pump is 1 L / h, the air volume is 72 CFM, the material stays for 3 seconds, and becomes a powder after preliminary drying. The powder is subjected to secondary drying through the discharge nozzle. The secondary drying temperature is 65°C, the inner diameter of the nozzle is 2.0 mm, and the material is settled in a collection bottle to obtain secondary polymer microspheres, i.e., polymer microspheres.

[0061] The glass transition temperatures Tg of the core and shell of the polymer microspheres, i.e., the primary polymer microspheres, were calculated based on the FOX formula. The core Tg was calculated to be 110°C, and the shell Tg was about 75-80°C (72.2°C without considering crosslinking).

[0062] The photo of the primary polymer microspheres obtained in step S2 is shown in Figure 1 The photo of the secondary polymer microspheres prepared in step S3 is shown in Figure 2 shown.

[0063] See also Figure 3 As shown, the particle size of the polymer microspheres was measured, and the results are shown in Table 1:

[0064] Table 1

[0065] Avgerage of Arithmetic Mean of all Measurements:0.311+ / -0.0001μm

[0066]

[0067] Example 2

[0068] This embodiment provides a method for preparing polymer microspheres, which is carried out as follows:

[0069] S1: 20g methyl methacrylate, 0.5g butyl acrylate, 0.5g methacrylic acid, and 100g water were mixed, nitrogen was passed through, high-speed stirring and shearing was performed at 9000r / min, and water bath heating was turned on (the temperature was set to 65°C). At 65°C, 20g aqueous solution containing 0.1g APS was added dropwise, and the reaction was allowed to react for 1.5h to generate seed microspheres to obtain a reaction solution;

[0070] S2: Add 120g methyl methacrylate, 10g isooctyl acrylate, 6g methacrylic acid, and 50g 1% APS solution to the reaction solution for 20 minutes, then drop 5g hydroxymethyl acrylamide, 2g hydroxyethyl acrylate, and 1g DVB, and keep warm at 64.8°C for 10 hours. At the same time, drop 10g aqueous solution containing 0.25g FF6 and 10g aqueous solution containing 0.2g APS, and keep warm for 2 hours after the drop is complete (due to the low temperature, add an oxidation-reduction system initiator to further promote the monomer reaction and improve the conversion rate). Filter the material through a 400-mesh filter to obtain a milky white emulsion, i.e., a microsphere emulsion;

[0071] S3: The microsphere emulsion obtained above is sent to a spray drying chamber for high-pressure atomization (funnel-shaped drying chamber with a volume of 4 L) by an intermittent peristaltic pump. The spray chamber temperature is set at 150°C, the atomization pressure is 0.6 MPa, and a plurality of atomizing nozzles are provided on the atomizing disk. The inner diameter of the nozzle is 0.7 mm, the feed rate of the peristaltic pump is 0.8 L / h, the air volume is 96 CFM, the material stays for 2 seconds, and becomes a powder after preliminary drying. The material is subjected to secondary drying through the discharge nozzle. The secondary drying temperature is 66°C, the inner diameter of the nozzle is 2.0 mm, and the material is settled in a collection bottle to obtain secondary polymer microspheres, i.e., polymer microspheres.

[0072] The glass transition temperatures Tg of the core and shell of the polymer microspheres, i.e., the primary polymer microspheres, were calculated based on the FOX formula. The core Tg was calculated to be 99°C, and the shell Tg was about 85-90°C (84.3°C without considering crosslinking).

[0073] See also Figure 4 As shown, the particle size of the polymer microspheres was measured, and the results are shown in Table 2:

[0074] Table 2

[0075] Avgerage of Arithmetic Mean of all Measurements: 0.254+ / -0.1168

[0076]

[0077] Example 3

[0078] This embodiment provides a method for preparing polymer microspheres, which is carried out as follows:

[0079] S1: 20g methyl methacrylate, 1g butyl acrylate, 0.2g sodium p-styrene sulfonate and 100g water were mixed, nitrogen was passed through, high-speed stirring and shearing was performed at 9000r / min, and water bath heating was started (the temperature was set to 70°C). At 70°C, 20g aqueous solution containing 0.22g APS was added dropwise, and a slightly blue color appeared in the reaction, and seed microspheres were generated to obtain a reaction solution;

[0080] S2: Adjust the stirring speed to 200r / min, add 100g methyl methacrylate, 30g butyl acrylate, 3g acrylic acid, 50g APS solution with a mass fraction of 1.2% to the reaction solution and react for 20 minutes, then drop 5g hydroxymethyl acrylamide, 2g hydroxyethyl acrylate, and 2g DVB, and keep warm at 70°C for 10 hours. Filter the material through a 300-mesh filter to obtain a milky white emulsion, i.e., microsphere emulsion;

[0081] S3: The microsphere emulsion obtained above is sent to a spray drying chamber for high-pressure atomization (funnel-shaped drying chamber with a volume of 4 L) by an intermittent peristaltic pump. The spray chamber temperature is set at 120°C, the atomization pressure is 0.7 MPa, and a plurality of atomizing nozzles are provided on the atomizing disk. The inner diameter of the nozzle is 0.7 mm. The peristaltic pump feed rate is 1 L / h, the air volume is 96 CFM, and the material stays for 3 seconds. After preliminary drying, it becomes a powder and is secondary dried through the discharge nozzle. The secondary drying temperature is 60°C, the inner diameter of the nozzle is 2.0 mm, and the material is settled in a collection bottle to obtain secondary polymer microspheres, i.e., polymer microspheres.

[0082] The glass transition temperatures Tg of the core and shell of the polymer microspheres, i.e., the primary polymer microspheres, were calculated based on the FOX formula. The core Tg was calculated to be 90°C, and the shell Tg was about 55-60°C (54.0°C without considering crosslinking).

[0083] Comparative Example 1

[0084] This comparative example provides a method for preparing polymer microspheres, which is carried out as follows:

[0085] S1: 20g methyl methacrylate, 1g butyl acrylate, 1g methacrylic acid, and 100g water were mixed, nitrogen was passed through, high-speed stirring and shearing was performed at 8000r / min, and water bath heating was started (the temperature was set to 70°C). At 70°C, 20g aqueous solution containing 0.1g APS was added dropwise, and the mixture was reacted for 1h to generate seed microspheres to obtain a reaction solution;

[0086] S2: Add 120g methyl methacrylate, 20g butyl acrylate, 4g acrylic acid, and 80g KPS solution with a mass fraction of 0.5% to the reaction solution and react for 30 minutes, then drop 10g hydroxyethyl acrylamide and 2g DVB, and keep warm at 70°C for 10 hours. Filter the material through a 300-mesh filter to obtain a milky white emulsion, i.e., a microsphere emulsion;

[0087] S3: Dry the microsphere emulsion obtained above in a vacuum drying oven at 60° C. and 19 kPa to obtain polymer microspheres.

[0088] Comparative Example 2

[0089] This comparative example provides a method for preparing polymer microspheres, which is carried out as follows:

[0090] S1: 120g methyl methacrylate, 20g butyl acrylate, 4g acrylic acid, and 100g water were mixed, nitrogen was passed through, high-speed stirring and shearing was performed at 8000r / min, and water bath heating was started (the temperature was set to 70°C). At 70°C, 20g aqueous solution containing 0.1g APS was added dropwise, and the mixture was reacted for 1h to generate seed microspheres to obtain a reaction solution;

[0091] S2: Add 20g methyl methacrylate, 1g butyl acrylate, 1g methacrylic acid, and 80g KPS solution with a mass fraction of 0.5% to the reaction solution and react for 30 minutes, then drop 10g hydroxyethyl acrylamide and 2g DVB, and keep warm at 70°C for 10 hours. Filter the material through a 300-mesh filter to obtain a milky white emulsion, i.e., a microsphere emulsion;

[0092] S3: The microsphere emulsion obtained above is sent to a spray drying chamber for high-pressure atomization (funnel-shaped drying chamber with a volume of 4 L) by an intermittent peristaltic pump. The gradient temperature of the spray chamber is set to 130°C, the atomization pressure is 0.5 MPa, and a plurality of atomizing nozzles are provided on the atomizing disk. The inner diameter of the nozzle is 0.5 mm, the feed rate of the peristaltic pump is 1 L / h, the air volume is 72 CFM, the material stays for 3 seconds, and becomes a powder after preliminary drying. The powder is subjected to secondary drying through the discharge nozzle. The secondary drying temperature is 65°C, the inner diameter of the nozzle is 2.0 mm, and the material is settled in a collection bottle to obtain secondary polymer microspheres, i.e., polymer microspheres.

[0093] Comparative Example 3

[0094] This comparative example provides a method for preparing polymer microspheres, which is carried out as follows:

[0095] S1: 20g methyl methacrylate, 1g butyl acrylate, 1g methacrylic acid, and 100g water were mixed, nitrogen was passed through, high-speed stirring and shearing was performed at 8000r / min, and water bath heating was started (the temperature was set to 70°C). At 70°C, 20g aqueous solution containing 0.1g APS was added dropwise, and the mixture was reacted for 1h to generate seed microspheres to obtain a reaction solution;

[0096] S2: The reaction liquid obtained above is sent to a spray drying chamber for high-pressure atomization (funnel-shaped drying chamber with a volume of 4 L) by an intermittent peristaltic pump. The gradient temperature of the spray chamber is set to 130°C, the atomization pressure is 0.5 MPa, and a plurality of atomizing nozzles are provided on the atomizing disk. The inner diameter of the nozzle is 0.5 mm. The peristaltic pump feed rate is 1 L / h, the air volume is 72 CFM, and the material stays for 3 seconds. After preliminary drying, it becomes a powder and is secondary dried through the discharge nozzle. The secondary drying temperature is 65°C, the inner diameter of the nozzle is 2.0 mm, and the material is settled in a collection bottle to obtain secondary polymer microspheres, i.e., polymer microspheres.

[0097] The properties of the polymer microspheres prepared in the above embodiments and comparative examples were tested, and the testing method was as follows:

[0098] 1. Dissolution and swelling test: Disperse the polymer microsphere powder in water to make a slurry and place it in a tetrafluoroethylene mold. Dry it at 120°C to form a film. Cut part of the film, weigh the mass m0, soak it in a mixed electrolyte solvent (ethylene carbonate (EC): diethyl carbonate (DEC): dimethyl carbonate (DMC) volume ratio 1:1:1), soak it at 90°C for 1h, take out the film, gently wipe off the surface liquid, and weigh the mass m1. Dry the film in an oven at 120°C, weigh the final mass m2, and calculate the dissolution and swelling according to the following formula.

[0099] Swelling = (m1-m0) / m0*100% Dissolution = (m2-m0) / m0*100%

[0100] 2. Hot-pressing peel strength test: 10 parts of microsphere powder, 7 parts of polyacrylate binder (Derby DA-9250), 1.5 parts of sodium carboxymethyl cellulose, 0.3 parts of polyether siloxane wetting agent, 0.6 parts of dispersant and appropriate amount of water are used to make a mixture slurry by ball milling (speed 580r / min, ball milling for 1h). The mixed slurry is coated on the PP diaphragm substrate to form a wet film coating with a thickness of 6-9um, and fully dried at 60°C to obtain a single-sided mixed functional diaphragm. Subsequently, the coating layer is hot-pressed and qualitatively bonded to the positive electrode (hot-pressing temperature 80±1°C, pressure 0.25MPa, time 20s), and a 180° peel strength test is performed on a tensile machine.

[0101] The test results are shown in Table 3:

[0102] Table 3

[0103]

[0104] It can be seen from the data in the above table that the polymer microspheres prepared in various embodiments of the present invention have the advantages of high bonding strength, small swelling in electrolyte, and good hot pressing effect after being used in the separator.

[0105] The difference between Comparative Example 1 and Example 1 is that the primary polymer microspheres are not subjected to high-temperature atomization drying, and the prepared polymer microspheres only have small-size microspheres and irregular aggregates formed by agglomeration and bonding between some microspheres during the drying process, and no secondary large-size microspheres are generated, resulting in low bonding strength and poor hot pressing effect.

[0106] The difference between Comparative Example 2 and Example 1 is that the monomers in step S1 and step S2 are interchanged, and the prepared polymer microspheres only have small-particle-size microspheres. Since the Tg of the primary microsphere shell is relatively large, effective agglomeration and bonding cannot be formed during the high-temperature atomization drying process, no secondary large-particle-size microspheres are generated, the swelling in the electrolyte is large, and the hot pressing effect is poor.

[0107] The difference between Comparative Example 3 and Example 1 is that the soft shell structure is not introduced on the outside of the seed microspheres, and the prepared polymer microspheres have only small particle size microspheres with a D50 of 0.2 μm. Due to the high Tg of the primary microspheres, they cannot be bonded to form secondary large particle size microspheres during the high temperature atomization drying process, no secondary large particle size microspheres are generated, the swelling in the electrolyte is large, and the hot pressing effect is poor.

[0108] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A polymer microsphere, characterized in that: It comprises a core body and a shell covering the outer side of the core body; wherein the glass transition temperature of the shell is lower than the glass transition temperature of the core body; and the glass transition temperature range of the shell is 50°C-100°C; The glass transition temperature of the core body ranges from 90°C to 120°C; The preparation method of the polymer microspheres comprises the following steps: S1: Using soft monomer and hard monomer in a mass ratio of 1:(20-45) as raw materials, seed microspheres were generated by soap-free emulsion polymerization; S2: using the seed microsphere as the core, copolymerizing the soft monomer and the hard monomer in a mass ratio of 1:(3-13) to form a microsphere emulsion; S3: using the microsphere emulsion as a raw material and adopting a high temperature atomization drying process to prepare polymer microspheres; The outer diameter of the polymer microspheres is (4.5-5.5) μm; The soft monomers in step S1 and step S2 are both selected from at least one of butyl acrylate and isooctyl acrylate; The hard monomers in step S1 and step S2 are both selected from at least one of methyl methacrylate, styrene, acrylonitrile, sodium p-styrene sulfonate, acrylic acid, and methacrylic acid.

2. The polymer microspheres according to claim 1, characterized in that: Step S1 includes: mixing the soft monomer, the hard monomer and water according to the formula, stirring and shearing in an inert gas atmosphere, heating to 60-80° C., dropping an initiator, reacting, generating seed microspheres, and obtaining a reaction solution.

3. The polymer microspheres according to claim 2, characterized in that Step S2 comprises: adding a soft monomer, a hard monomer and an initiator to the reaction solution according to the formula amount, and after the reaction, dripping a crosslinking agent, and continuing the reaction to obtain a microsphere emulsion.

4. The polymer microspheres according to claim 1, characterized in that The atomization drying temperature of the high temperature atomization drying process in step S3 is 60°C-200°C.

5. A lithium ion battery separator, characterized in that: The invention comprises the polymer microspheres as described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Water-based binder, modified diaphragm, battery and preparation method of water-based binder

    CN115260403A

  • Preparation method of emulsion type binder and application of emulsion type binder in negative electrode of lithium ion battery

    CN115850591A

  • Diaphragm and secondary battery

    CN116666905A